Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Sums of second order and the value of mathematics

  1. Mar 22, 2004 #1


    User Avatar
    Homework Helper

    Consider this sequence:

    1, 2, 3, 4, 5, ...

    We can calculate the n'th term of the sequence by the function t(n) = n. We could define s(n), the sum to n terms, recursively as s(1) = 1 and s(n) = n + s(n-1). The time bound of this procedure is O(n), but it isn't efficient because we can find an O(1) formula: s(n) = n(n+1)/2

    Now consider this sequence:

    1, 3=(1+2), 6=(1+2+3), 10, 15, 21, ...

    Here the n'th term of the sequence is given by s(n) = n(n+1)/2, the same function as above. We can define u(n), the sum to n terms of this sequence, recursively as u(1) = 1 and u(n) = u(n) + s(n-1). This procedure has a time bound of O(n).

    Can we do better than this? We can use simple variations, but the time stays linear. For example, where n>2, 'u(n) = u(n-2) + 2.s(n-1) + n' could be used. This nearly doubles the speed on average, but the time taken is still proportional to n.

    Is there a method to calculate this sum in time less than proportional to n? As a matter of fact, we can do it in time which is O(logn).

    s(n) = n(n+1)/2.

    Where n = 1: u(1) = 1
    Where n is even: u(n) = 2.u(n/2) + n.s(n/2)
    Where n is odd: s2(n) = 2.u((n-1)/2) + ((n+1)/2) * [s((n-1)/2) + s((n+1)/2)]

    In case you are wondering how I came up with these formulas, notice that (1) below corresponds to u(4). It can be split up into (2), which corresponds to 'u(2) + 2.s(2) + 3 + (3+4)'. In (3) you can see that '3 + (3+4)' can be split into u(2) + 2.s(2)

    1: 1 + (1+2) + (1+2+3) + (1+2+3+4)

    2: 1 + (1+2)
    + (1+2) + (1+2)
    + 3 + (3+4)

    3: 3 + (3+4)
    = 1 + (1+2)
    + 2 + (2+2)

    Putting it together:

    u(4) = u(2) + 2.s(2) + u(2) + 2.s(2)
    = 2.u(2) + 2.(2.s(2))

    This corresponds to:

    u(n) = 2.u(n/2) + (n/2)(2.s(n/2))
    = 2.u(n/2) + n.s(n/2)

    I derived the formula for when n is odd the same way. I will now generalise this method to work for all arithmetic series:

    t(n) = a+(n-1)d
    s(n) = (n/2)[2a+(n-1)d]

    f(n) = n(n+1)/2

    where n = 1: g(n) = 1
    where n is even: g(n) = 2.g(n/2) + n.f(n/2)
    where n is odd: g(n) = 2.g((n-1)/2) + ((n+1)/2) * [f((n-1)/2) + f((n+1)/2)]

    s2(n) = a.f(n) + d.g(n-1)

    Let's call this the 'second sum'. I wonder whether it is possible to find a formula for the 2nd sum that isn't recursive. I don't think the 'second sum' as I have defined it has any application, because I can't envision any place where the second sum might be useful. Can this be applied somewhere? What about the 3rd or 4th sum?

    Mathematics is only useful where it can be applied, or so I think. Does mathematics attain value only when you can apply it? This question is more philosophical than mathematical, I think. Is it only worthwhile to find formulas for such abstract things as the 'second sum' when we see the need for them?

    The point of this post is because I don't see the value of such abstract things, unless they can be applied. Is this fair?
  2. jcsd
  3. Mar 22, 2004 #2
    You can find the "second sum", but there's no fixed formula for it.

    Each term in the series:
    1, 3=(1+2), 6=(1+2+3), 10, 15, 21, ...
    Is given by the formula:
    [tex]a_{(n)} = \frac{n(n + 1)}{2} = \frac{1}{2}(n^2 + n)[/tex]
    To find the sum of these terms, you need to find the sum of n times [itex]n^2[/itex], n times [itex]n[/itex], add them together and divide by two.

    The sum of n times [itex]n[/itex] is simple, and you already found it yourself:
    [tex]{S_1}_{(n)} = \frac{n(n + 1)}{2}[/tex]
    It is the sum of n times [itex]n^2[/itex] you need to find now. I won't explain here how you get it (it's a bit length), but the formula is:
    [tex]{S_2}_{(n)} = \frac{n}{6}(2n + 1)(n + 1)[/tex]

    So the final "second sum" that you are looking for is:
    [tex]S_{(n)} = {S_1}_{(n)} + {S_2}_{(n)} = \frac{1}{2}(\frac{n}{2}(n + 1) + \frac{n}{6}(2n + 1)(n + 1))[/tex]
    You can simplify it if you want, but that's it. :smile:
  4. Mar 22, 2004 #3

    matt grime

    User Avatar
    Science Advisor
    Homework Helper

    You might find find learning about difference equations useful
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook